Social participation among older adults not engaged in full‐ or part‐time work is associated with more physical activity and less sedentary time. Issue 11 (23rd February 2017) - Kikuchi, Hiroyuki; Inoue, Shigeru; Fukushima, Noritoshi; Takamiya, Tomoko; Odagiri, Yuko; Ohya, Yumiko; Amagasa, Shiho; Oka, Koichiro; Owen, Neville
Abstract: Aim: Social participation provides health benefits for older adults. However, there is the need to identify whether higher social participation is associated with older adults being more physically active and less sedentary (sitting time). We examined the associations of social participation with physical activity, and sedentary time, in a population‐based sample of older Japanese adults. Methods: A population‐based, cross‐sectional mail survey carried out in 2010 was used to collect data on social participation, physical activity, sedentary time and sociodemographic characteristics. Data were examined from 1146 community‐dwelling, unemployed older adults (mean age 70.1 years, 43% men). Multivariate logistic regression analyses were used to calculate odds ratios (OR) for associations of social participation with physical activity and total sedentary time; and, for associations with passive and mentally‐active sedentary (sitting) time. Results: For both men and women, those with higher social participation were more physically active (OR 2.10, 95% CI 1.44–3.06 among men; OR 1.93, 95% CI 1.39–2.68 among women). Total sedentary time had significant associations among men (OR 0.62, 95% CI 0.42–0.90), but not among women (OR 0.80, 95% CI 0.58–1.11). Social participation was associated with less passive sedentary time (OR 0.55, 95% CI 0.38–0.81 for men; OR 0.72, 95% CI 0.51–0.99 for women). Conclusions: Promoting social participation among older adults could contribute to increasing physical activity and reducing sedentary time, with potential benefits for chronic disease. Further research is required to elucidate the deleterious and beneficial roles of passive and mentally‐active sedentary time for older adults.Geriatr Gerontol Int 2017; 17: 1921–1927 .